The Illusion of the Recovery of Damages found by the Court of Audits, between the Limit of the Legal Rule and the Good Faith of the Audited Entity - Negrut, Vasilica; Zorzoana, Ionela Alina (Acta Universitatis Danubius. Juridica, 2024)
The current analysis originated from a question that frequently arose in practice. We can say with certainty that in 99% of cases, the prescription of the audited entity's right to recover the respective amounts intervenes. This is based on the attributions of the Romanian Court of Accounts, which notes the occurrence of damages in the patrimony of the audited entities and orders recovery measures. Additionally, the administrative documents issued by the audit institution are contested in administrative litigation, and the audited authorities lack any measures for the recovery of damages until the courts issue a definitive solution. Hence the challenge of solving these situations because, on the contrary, it can be determined that the recovery of these damages depends only on the good faith of the verified entities that can initiate damage recovery actions concurrently with the actions whose goal is to challenge the administrative documents issued by the Court of Accounts, in order to prevent the intervention of the statute of limitations sanction. To find inspiration for a potential de lege ferenda proposal, we will highlight the rules pertaining to the courts of accounts in other European states. Concurrently, in order to provide a comparative legal note to this study, we will illustrate the theoretical components with instances drawn from national and European jurisprudence (where applicable) as well as from other EU members.